Applications Of Geographic Information Systems In Urban Land Use Planning In Malaysia - Samat, Narimah (2006)
Over the past forty years Geographic Infonnation Systems (GIS) have been used in many planning applications ranging from daily administrative operations to strategic planning functions such as evaluating socio-economic data in land use allocation tasks.